2019
DOI: 10.30534/ijatcse/2019/107842019
|View full text |Cite
|
Sign up to set email alerts
|

Interface for the Factor-inclusion Weighting Approach in Determining the Number of Multipath Propagation Clusters

Abstract: Design and development of MIMO communication systems require a comprehensive analysis of channel characteristics. In real-world applications, the channel consists of randomly propagating signals that travel in two or more paths called multipaths. Literature shows an approach of analyzing the channel, which is knowing the number of clusters or groupings of these multipaths. This paper presents a development of an interface featuring a factor weighing approach in determining the number of clusters. Different vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…One challenge of clustering is also to find the number of optimal clusters. Moreover, a graphical user interface (GUI) was developed in [15] to determine cluster counts by a factor weighing approach, and it was reported that the delay and angular data were effective weight factors in the indoor and semi-urban scenarios, respectively. The non-stationary and spherical waveform was considered parameters in [16].…”
Section: Multipath Clusteringmentioning
confidence: 99%
“…One challenge of clustering is also to find the number of optimal clusters. Moreover, a graphical user interface (GUI) was developed in [15] to determine cluster counts by a factor weighing approach, and it was reported that the delay and angular data were effective weight factors in the indoor and semi-urban scenarios, respectively. The non-stationary and spherical waveform was considered parameters in [16].…”
Section: Multipath Clusteringmentioning
confidence: 99%
“…Over the past two decades, clustering of MPCs [1]- [2] gained much attention in the research community and is now the basis of various channel models nowadays such as the European Cooperation in Science and Technology (COST) 259, COST 2100, 3GPP Spatial Channel Model, and the European Wireless World Initiative New Radio (WINNER) due to the correspondence of the majority of the signals apart from the line-of-sight to form as significant clusters of signal energy. Various parameters of MPCs such as the angular spreads, delay, number, and position are used in the clustered structure modeling to group MPCs into clusters.…”
Section: Introductionmentioning
confidence: 99%
“…The interface is an effective method in visualizing the COST 2100 dataset and the clustering results. A previous work [17] on GUI can visually analyze the reference data and the calculated clusters but considered only the cluster count. In this work, the GUI can be used by the user to visualize, manipulate, and analyze the multipaths generated by the COST 2100 channel model (C2CM) and the clustering results of MSCAMSMA not only giving the accuracy on the number of clusters but also the membership of clusters.…”
Section: Introductionmentioning
confidence: 99%